ANALISIS FAKTOR YANG MEMPENGARUHI PRODUKTIVITAS KERJA PEGAWAI PADA MASA PANDEMI COVID-19 - Encep Saefullah; Tabroni Tabroni (National Conference on Applied Business, Education, & Technology (NCABET), 2021)
The purpose of this study was to determine the most dominant factors affecting employee work productivity in Carita District, Pandeglang Regency during the Covid-19 Pandemic. The data collection method used in this research is the questionnaire method, while the analysis method uses a Likert scale and rating scale. Of the three factors that affect Employee Work Productivity in Carita Subdistrict, Pandeglang Regency during the Covid-19 Pandemic, namely Education and Training received perceptions from respondents with agreed criteria, while Motivation received perceptions from respondents with strongly agree criteria meaning that these three factors affect employee work productivity. The most dominant factor influencing Employee Work Productivity in Carita Subdistrict, Pandeglang Regency during the Covid-19 Pandemic is Motivation, because it has the highest average value among the other two factors, namely 175.5, this shows that motivation has an important role and is a condition self-directed employees to achieve organizational goals